Relative efficiency of the public transit in costa rica. Bus interregional routes, 2009 - Navarro-Rodríguez, David (2017)
This article represents an application of frontier models for the evaluation of the relative technical efficiency in the regulated public transport sector in Costa Rica. Using data from a survey made by Autoridad Reguladora de Servicios Públicos (ARESEP) in 2009 a data envelopment analysis (DEA) model was computed to obtain the relative efficiency for the public service provided in interregional public transit routes around the country. As output variables, the number of passenger for kilometer of travel and monthly average of passenger per bus were used. As input variables, we used the spending of many key aspects to provide the service. Based on the model, the 29 interregional routes were classified and ranked by their respective efficiency. In addition, for those classified as inefficient, some enhancement factors were provided.